To compute the distance between the points \( B(-2, -6) \) and \( C(10, -1) \), we can use the distance formula, which is given by:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Here, we have:
- \( (x_1, y_1) = (-2, -6) \)
- \( (x_2, y_2) = (10, -1) \)
Now we can plug in the values:
\[ d = \sqrt{(10 - (-2))^2 + (-1 - (-6))^2} \]
Calculating inside the parentheses first:
\[ d = \sqrt{(10 + 2)^2 + (-1 + 6)^2} \] \[ d = \sqrt{(12)^2 + (5)^2} \] \[ d = \sqrt{144 + 25} \] \[ d = \sqrt{169} \] \[ d = 13 \]
Therefore, the distance between points \( B \) and \( C \) is \( 13 \) units.